2018
DOI: 10.3748/wjg.v24.i33.3681
|View full text |Cite
|
Sign up to set email alerts
|

From bench to bedside: Fecal calprotectin in inflammatory bowel diseases clinical setting

Abstract: Fecal calprotectin (FC) has emerged as one of the most useful tools for clinical management of inflammatory bowel diseases (IBD). Many different methods of assessment have been developed and different cut-offs have been suggested for different clinical settings. We carried out a comprehensive literature review of the most relevant FC-related topics: the role of FC in discriminating between IBD and irritable bowel syndrome (IBS) and its use in managing IBD patients In patients with intestinal symptoms, due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
116
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(129 citation statements)
references
References 114 publications
2
116
0
2
Order By: Relevance
“…However, low‐grade inflammation was observed in this model, while no morphological signs of inflammation and anatomical alterations were detected, and the sensitive marker faecal Lcn‐2 was increased in this model, as previously described (Chassaing et al, ). Such low‐grade inflammation has been described in patients (Ford & Talley, ; Linedale & Andrews, ; Mumolo et al, ; Vivinus‐Nébot et al, ).…”
Section: Discussionmentioning
confidence: 89%
“…However, low‐grade inflammation was observed in this model, while no morphological signs of inflammation and anatomical alterations were detected, and the sensitive marker faecal Lcn‐2 was increased in this model, as previously described (Chassaing et al, ). Such low‐grade inflammation has been described in patients (Ford & Talley, ; Linedale & Andrews, ; Mumolo et al, ; Vivinus‐Nébot et al, ).…”
Section: Discussionmentioning
confidence: 89%
“…The (37). F-calprotectin has been reported as a marker for the differentiation between IBS and inflammatory bowel diseases (16,17), and as a potential biomarker for the severity of IBS (12). Measurable F-calprotectin levels were most often noted in participants who experienced incomplete evacuation when defecating, and in participants with a higher degree of constipation.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma levels of calprotectin have been hypothesized to serve an important role in a number of gynaecological conditions, including cervical inflammation (14,15). F-calprotectin is the biomarker with the highest sensitivity for local inflammation in the GI tract (16,17). To the best of our knowledge, calprotectin has not been previously measured in faecal samples of patients with endometriosis, although intestinal involvement is often noted in this disease (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…It is released from cells during cell activation or death, and it is stable in feces for several days after excretion [38]. This has been shown to be a sensitive marker of activity both in CD and in Ulcerative Colitis (UC); it is the stronger inflammatory marker predictor of relapse in those people as well [39].…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…It is a common finding especially in developed countries: by the age of 85, the large majority of the population living in developed countries will have developed colonic diverticula [1]. Recent ?epidemiology studies found different prevalence in European countries according to socioeconomic status: countries with a lower socioeconomic status report a 5.3% frequency of diverticulosis in patients aged [30][31][32][33][34][35][36][37][38][39]8.7% in those aged [40][41][42][43][44][45][46][47][48][49]19.4% between 50 and 59, and up to 29.6% in subjects over the seventh decade, while maximal incidences were found in patients aged 70-79 and above 80 of 40.2% and 57.9%, respectively [2]. Although diverticulosis prevalence in Africa and Asia remains low, more recent epidemiology studies found its prevalence increasing also in the developing world, probably because of changes in lifestyle [2].…”
Section: Introductionmentioning
confidence: 99%